1944
DOI: 10.1192/bjp.90.379.554
|View full text |Cite
|
Sign up to set email alerts
|

Some Problems Arising from a Study of Mental Patients Over the Age of Sixty Years

Abstract: It is generally known that in recent years there has been a considerable increase of the elderly population. In addition, we assume that unless the birth-rate rises again, an increasing proportion of the population will be found in the involutional and senile periods of life. This development has already begun; whereas in 1901 7.6 per cent. of the population of Scotland were over 60 years of age, the percentage in 1941 has been estimated at 13.0. Men are less long lived than women, the figures being 6.6 and 8.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

1968
1968
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 6 publications
0
19
0
Order By: Relevance
“…One surveyed his older patients, concluding that their mental illnesses were not inevitable, that depressive illness could be distinguished from dementia and that interventions could help (Post 1944). Successful treatment of depressed older people using the new electroconvulsive therapy (ECT) (Mayer-Gross 1945, p. 101) and evidence that social interventions could prevent admission and enable discharge of confused older people (Lewis and Goldschmidt 1943) surprised the clinicians.…”
Section: Research and Innovation: Challenging Medical Doctrine About mentioning
confidence: 99%
“…One surveyed his older patients, concluding that their mental illnesses were not inevitable, that depressive illness could be distinguished from dementia and that interventions could help (Post 1944). Successful treatment of depressed older people using the new electroconvulsive therapy (ECT) (Mayer-Gross 1945, p. 101) and evidence that social interventions could prevent admission and enable discharge of confused older people (Lewis and Goldschmidt 1943) surprised the clinicians.…”
Section: Research and Innovation: Challenging Medical Doctrine About mentioning
confidence: 99%
“…Cerebro-vascular incidents, like other incisive physical disorders, sometimes precipitate depressive states. There may even be an indirect aetiological relationship between cerebro-vascular disease and the depressive diathesis (Post, 1962). But, on the basis of recent long-term follow-up studies, it can be stated categorically that elderly depressives do not develop de novo either senile dementia or arteriosclerotic brain disease any more frequently than the elderly population as a whole (Kay et al, 1955;Kay, 1962;Post, 1962).…”
Section: Affective Illnessesmentioning
confidence: 99%
“…Lesions in these areas merely produce emotional lability, and forced or paradoxical laughing and crying. For the following reasons it is suggested that in the case of depressive illnesses the brain damage acts as a stress which mobilizes or facilitates the affective mental reaction type: 'Organic' depression can be as severe as 'functional' depression, and is frequently indistinguishable on the basis of the affective state alone; most cerebral-arteriosclerotic depressives have suffered affective illnesses earlier in life, and/or have a positive family history for severe depression; the immediate results of treatment are equally good in 'organic' as in 'functional' depressives, using the same therapeutic agents (Post, 1962(Post, , 1965.…”
Section: Affective Illnessesmentioning
confidence: 99%
See 1 more Smart Citation
“…Active treatment to assist recovery from physical illness in old age was advocated by Marjory Warren, a geriatrician, in 1943, 23 and for mental illness by Felix Post, a psychiatrist, in 1944. 24 Despite that, specialist rehabilitation facilities, for example to enable discharge home for elderly people who have required inpatient treatment for physical conditions co-existing with psychiatric illness, remain a rarity. 25 In addition, failure to provide rehabilitation and often relatively low-cost, community management for long-term multi-factorial disability has humane and economic implications, since it may result in unnecessary long-stay institutional placement or high-cost crisis re-admissions to acute hospitals.…”
Section: Attitudes and Economicsmentioning
confidence: 99%